2011
DOI: 10.1175/2009jas2970.1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Outflow Environment on Tropical Cyclone Intensification and Structure

Abstract: In this study, the impacts of regions of weak inertial stability on tropical cyclone intensification and peak strength are examined. It is demonstrated that weak inertial stability in the outflow layer minimizes an energy sink of the tropical cyclone secondary circulation and leads to more rapid intensification to the maximum potential intensity. Using a full-physics, three-dimensional numerical weather prediction model, a symmetric distribution of environmental inertial stability is generated using a variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 37 publications
5
68
1
Order By: Relevance
“…16a and 16b), the primary differences are found just north and northwest of the storm, with weakening storms characterized by a broad trough to the north or northeast of the storm and much stronger westerlies extending to near the storm center, while strengthening storms are located south of a ridge with westerlies displaced farther northward. Outflow from the strengthening storms is stronger and broader, which may reflect the more vigorous convection in those cases or a favorable interaction with the trough located poleward and to the west of the storm (Holland and Merrill 1984;Molinari and Vollaro 1989;Rappin et al 2010). By day 2 (Figs.…”
Section: A Composite View Of the Sal And Hurricanesmentioning
confidence: 98%
“…16a and 16b), the primary differences are found just north and northwest of the storm, with weakening storms characterized by a broad trough to the north or northeast of the storm and much stronger westerlies extending to near the storm center, while strengthening storms are located south of a ridge with westerlies displaced farther northward. Outflow from the strengthening storms is stronger and broader, which may reflect the more vigorous convection in those cases or a favorable interaction with the trough located poleward and to the west of the storm (Holland and Merrill 1984;Molinari and Vollaro 1989;Rappin et al 2010). By day 2 (Figs.…”
Section: A Composite View Of the Sal And Hurricanesmentioning
confidence: 98%
“…Although these results confirm that interaction favors TC intensification in a statistical sense, to identify whether or not a particular trough interaction is conducive to TC intensification is still not straightforward (Hanley et al, 2001;Leroux et al, 2013). Besides, these two studies ignored the role of upper-level inertial stability, emphasized in a number of other studies (e.g., Holland and Merrill, 1984;Rappin et al, 2011).…”
Section: Tc Interactionmentioning
confidence: 77%
“…High inertial stability means that strong forcing will result in limited responses. As a TC intensifies, especially when doing so rapidly, it requires low inertial stability (e.g., Rappin et al, 2011); the higher inertial stability shown here is partially responsible for reducing the positive effect of large EFC. Another reason is that TC intensity change is also controlled by two other environmental factors, i.e., SST and VWS.…”
Section: Relationship Between Efc and Other Environmental Factorsmentioning
confidence: 79%
See 2 more Smart Citations